2007
DOI: 10.1177/0269215507077285
|View full text |Cite
|
Sign up to set email alerts
|

Apraxia of speech: how reliable are speech and language therapists' diagnoses?

Abstract: Despite controversy over its nature and existence, specialist speech and language therapists show high levels of agreement on the diagnosis of apraxia of speech using their clinical judgement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Specifically, we identified regions in cortical motor and somatosensory areas that predict AOS errors, even after removing variability explained by errors that could also occur in aphasia (and vice versa). The study of AOS has been built on different definitions of the disorder, 39–41 complicating the interpretation of findings regarding its localization and theoretical bases, and hindering the generalizability of conclusions pertaining to speech motor planning in general. On the most fundamental level, the current practices for AOS diagnosis are largely ambiguous and subject to variability in interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we identified regions in cortical motor and somatosensory areas that predict AOS errors, even after removing variability explained by errors that could also occur in aphasia (and vice versa). The study of AOS has been built on different definitions of the disorder, 39–41 complicating the interpretation of findings regarding its localization and theoretical bases, and hindering the generalizability of conclusions pertaining to speech motor planning in general. On the most fundamental level, the current practices for AOS diagnosis are largely ambiguous and subject to variability in interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have examined speech errors in patients with an aphasia consequent to stroke (Ackermann & Riecker, 2004; Dronkers, 1996; Mumby, Bowen, & Hesketh, 2007; Peach & Tonkovich, 2004; Riecker et al, 2004). Apraxia of speech has been well documented in stroke patients (Dronkers, 1996), and other authors have explicitly compared errors of speech production in patients with fluent vs. nonfluent aphasia due to stroke (Canter et al, 1985; Romani et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, consistency of diagnosis on the basis of clinical impression is far from good. While one recent study reported high consistency (Mumby et al, 2007), another reported staggering levels of inconsistency, at least when criteria were not specifically calibrated . Secondly, consistency, in itself, does not imply correct diagnosis.…”
Section: Introductionmentioning
confidence: 98%